Efficiency of combinative salicylic acid and chitosan preharvest-treatment on antioxidant and phytochemicals of ready to eat daikon sprouts during storage. (30th June 2019) - Supapvanich, Suriyan; Anan, Wassana; Chimsonthorn, Vathida
Highlights: 2.0 mM salicylic acid enhanced and maintained bioactive compounds in daikon sprout. 0.1% chitosan increased antioxidant activity and bioactive compounds in daikon sprout. SA + Chitosan enhanced free radical scavenging activity more than SA and chitosan. SA + Chitosan SA preserved total phenols concentration and enhance ascorbic acid. SA + Chitosan SA induced CAT activity more than SA and chitosan alone. Abstract: Effects of salicylic acid (SA), chitosan and combinative SA and chitosan (SA + Chitosan) preharvest-treatments on bioactive compounds improvement of daikon sprouts during cold storage (5 ± 1 °C) were investigated. In preliminary experiment, 2.0 mM SA and 0.1% chitosan treatments were best concentration in improving antioxidant activity and bioactive compounds of the sprouts during storage. In the main experiment, the effects of SA + Chitosan treatment on visual appearance, antioxidant activity, phytochemicals and antioxidant enzymes of the sprouts were monitored during storage. Visual appearance and pigments contents did not significantly change throughout storage. SA + Chitosan treated sprouts contained total phenols, ascorbic acid, antioxidant enzymes and antioxidant activity higher that control. Compared to SA and chitosan, SA + Chitosan enhanced total phenols, ascorbic acid, catalase activity and free radical scavenging activity during storage. In conclusion, SA + Chitosan could be a good mean enhancing phytochemicals of daikon sprouts during cold storage.